Framing the Litterbug: Picturing and Policing Public Cleanliness in Mid-Twentieth Century Philadelphia. (November 2022) - Hankins, Kristin
In early and mid-twentieth century American cities, visual culture announced the emergence of a new category of urban waste: litter. As anti-litter efforts used photography, cartoons, and other images to define litter, they also framed responsibility for its production and removal. This article focuses on the circulation of photographs in mid-twentieth century Philadelphia newspapers to illuminate the central role of visual culture in disciplining city dwellers about the proper relationship with litter and the larger landscape it marred. Early litter photography initially framed women, sanitation workers, and scavengers as primarily responsible for the production of litter. However, the disciplinary gaze sharpened in this set of images rippled outward as litter policing became increasingly formalized and punitive. As photographs defined and policed litter, they also illuminated a changing relationship between the municipal government and urban dwellers, in which residents were increasingly expected to maintain public space through unpaid physical labor and surveillance.